Blueprinting Photothermal Shape‐Morphing of Liquid Crystal Elastomers. Issue 17 (16th March 2020) - Kuenstler, Alexa S.; Chen, Yuzhen; Bui, Phuong; Kim, Hyunki; DeSimone, Antonio; Jin, Lihua; Hayward, Ryan C.
Abstract: Liquid crystal elastomers (LCEs) are an attractive platform for dynamic shape‐morphing due to their ability to rapidly undergo large deformations. While recent work has focused on patterning the director orientation field to achieve desired target shapes, this strategy cannot be generalized to material systems where high‐resolution surface alignment is impractical. Instead of programming the local orientation of anisotropic deformation, an alternative strategy for prescribed shape‐morphing by programming the magnitude of stretch ratio in a thin LCE sheet with constant director orientation is developed here. By spatially patterning the concentration of gold nanoparticles, uniform illumination leads to gradients in photothermal heat generation and therefore spatially nonuniform deformation profiles that drive out‐of‐plane buckling of planar films into predictable 3D shapes. Experimentally realized shapes are shown to agree closely with both finite element simulations and geometric predictions for systems with unidirectional variation in deformation magnitude. Finally, the possibility to achieve complex oscillatory motion driven by uniform illumination of a free‐standing patterned sheet is demonstrated. Abstract : Light‐driven shape‐morphing via spatially patterned photothermal deformation of liquid crystal elastomers is demonstrated. Distinct from shape prescription via modulation of the director orientation, a general method for patterning deformation profiles in monodomain elastomers with a unidirectional director field is presented. A model for prescribing Gaussian curvature via continuous deformation profiles is presented and validated with experiments and finite element analysis.